1995
DOI: 10.5254/1.3538757
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Vulcanization of Simple Model Olefins, Part IV: Vulcanizations of 2,3-Dimethyl-2-Butene with TMTD and Activated Zinc Dithiocarbamate/Xanthate Accelerators at Different Temperatures

Abstract: The mechanism of the accelerated sulfur vulcanization of rubber was studied by the use of 2,3-dimethyl-2-butene (C6H12, TME) as a simple, low-molecular model alkene. Treatment of TME with a mixture of ZnO, S8 and the classical accelerator TMTD at temperatures above 100°C yields a mixture of addition products ((C6H11—Sn—C6H11) ). In the temperature range of 50 up to 100 °C only intermediate products, C6H11—Sn—S(S)CN(CH3)2 are obtained. Room temperature vulcanization is feasible using highly reactive accelerator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…64 Various structures formed in sulfur vulcanized natural rubber is shown in Scheme 12. [70][71][72] The chemical probe work has allowed characterization and quantification of the number of mono, di and poly sulphidic crosslinks. -Generalized structures in sulfur vulcanized natural rubber.…”
Section: Accelerated Sulfur Vulcanizationmentioning
confidence: 99%
“…64 Various structures formed in sulfur vulcanized natural rubber is shown in Scheme 12. [70][71][72] The chemical probe work has allowed characterization and quantification of the number of mono, di and poly sulphidic crosslinks. -Generalized structures in sulfur vulcanized natural rubber.…”
Section: Accelerated Sulfur Vulcanizationmentioning
confidence: 99%
“…22,23,49 Weak resonances in the NMR at 0.98 -0.99 and 1.33-1.34 ppm show the formation of trace amounts of alkyl alkenyl and bis(alkyl) sulfides. As reported earlier, 22,29,33 HPLC analysis showed that no pendant groups, which are readily detected in TMTD accelerated systems, 16,22,24,49 were observed at any stage in the reaction. The Zn 2 (dmtc) 4 The loss for complete conversion to ZnS is 68.25%.…”
Section: Effect Of Water On Vulcanization Of Tme/zn 2 (Dmtc) 4 /Sulfurmentioning
confidence: 63%
“…Tagged TMTD and Zn 2 (dmtc) 4 exchange at elevated temperatures, 14 which is under conditions where tetramethylthiuram polysulfides (TMTPs) can form. [2][3][4]15,16 McCleverty et al 17 also reported ligand exchange at elevated temperatures. Recent evidence for sulfur-rich zinc(II) complexes was demonstrated in theoretical density functional calculations, where it was also shown that the addition of further sulfur atoms to the zinc dithiocarbamate chelate ring is energetically more favorable than insertion of the first sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…A 1 : 1 mixture of a zinc(II) bis-(isopropylxanthate) [Zn(ipxt) 2 ] and bis-(pentamethylene dithiocarbamato)piperidine Zn(II) [Zn(pmtc) 2 •(pip)] accelerator system can vulcanize rubber at room temperature. 8 This article presents the results of a study on the use of xanthate accelerators for vulcanization of NR at various temperatures and the effect of the temperature of curing on the mechanical properties of the vulcanizates.…”
Section: Introductionmentioning
confidence: 99%